Percepção de estudantes da saúde acerca do papel da espiritualidade na processo de saúde-doença - Lopes, Agatha Moura (Universidade Federal de São Carlos, 2024)
This article discusses the importance of spirituality in health and the perception of health students about their preparation to address the topic. Spirituality has had a role recognized by the World Health Organization (WHO) since 1978, when it was included in the definition of health as a dimension that affects well-being. Studies show that spirituality can positively influence patient recovery, reducing anxiety and improving coping with illness. However, spirituality is often confused with religion, and it is necessary to differentiate between them: spirituality involves the search for meaning in life, while religion is linked to specific beliefs and practices. Despite the importance of spirituality in the healthcare context, many professionals encounter barriers, such as lack of training and discomfort with the topic. The reported study was carried out at the Federal University of São Carlos, with 71 Medicine, Physiotherapy, Nursing and Occupational Therapy students. Most students recognize the influence of spirituality on health, but almost half feel unprepared to address the topic with patients, which points to a deficiency in the academic curriculum. Although 85.9% of those interviewed consider it important to include spirituality in their training, only 29.6% had contact with the topic during their undergraduate studies. It is concluded that, despite the recognition of the importance of spirituality, there are gaps in the training of students, which can affect clinical practice and comprehensive patient care.
Perception of health students about the role of spirituality in health-disease process
Keywords: Espiritualidade; Saude; Ensino; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA